Construction and validation of a test of knowledge of contraceptive methods for adolescents - Cervantes Jácome, Karla Elisa (2021)
Background: Valid and reliable instruments are required to measure the level of information on contraceptive methods in adolescents to promote their correct use. Objective: To construct and validate a test of knowledge of contraceptive methods for adolescents between 15 and 19 years old. Method: A 36-item test was developed that included the different contraceptive methods and information on the characteristics, use, efficacy, advantages and disadvantages of these methods. Once validated by expert judges, a college in Ecatepec was randomly selected as data collection site. Students of the three school grades answered the test. Results: The test was applied to a total of 229 students between 15 and 19 years old (M = 16.22; SD = .978). The majority were women (66%), single (88.5%) and lived with their parents (62.9%). Of the 36 initial items, 31 showed discriminatory power between those who performed well on the test and those who did not. The difficulty index of the questionnaire was .45 and revealed a reliability index value of .739. Around 60% of the participants obtained a percentage below 50% of correct answers in the entire test. Only about 4% of participants got a percentage of correct responses higher than 70%. The categories of characteristics and use were those in which the participants performed best when answering 48% of these questions correctly. The worst was effectiveness, advantages and disadvantages with 33%. Conclusion: The test’s psychometric properties showed that it is a valid and reliable test for its application in Mexican adolescents. The results indicate that most adolescents of the simple do not have complete information about contraceptive methods and that they know the least about their effectiveness and side effects.